Analisis Nilai Tambah Jipang pada Usaha “Gareng Lutfi” di Desa Moolo Indah Kecamatan Tinanggea - Santoso, Dwi; Iswandi, R. Marsuki; Abdullah, Weka Gusmiarty (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2018)
This study is motivated by jipang cake which still uses rice as a raw material in its production process is found in the home industry, so it is still unknown how much-added value is cultivated. This study aims to determine the added value obtained from processing into jipang cake in the business of "Jipang Gareng Lutfi" in Moolo Indah Village, Tinanggea District, South Konawe Regency. This study was conducted in the home industry "Jipang Gareng Lutfi" in Moolo Indah Village, Tinanggea Sub District, South Konawe District. The location of this study was chosen purposively, where the study’s subject was the business owner "Jipang Gareng Lutfi". Primary data was collected by a direct interview that used questionnaire. Data were analyzed by Hayami method. The results showed that the added value of jipang cake in the home industry business "Jipang Gareng Lutfi" was Rp 14.283/kg in one production and added value in one-kilogram raw material was Rp 714,15. The magnitude added value of the jipang cake is due to the large difference between the value of the product and the price of raw materials (in the form of rice) and the conversion factor. The product value is Rp 32.403 while the raw material price is only Rp 8,500 with a conversion factor of 1,52. This condition has an impact on the value-added ratio of the business "Jipang Gareng Lutfi" of 44,08% (high category). The results of the study also showed the benefits of labor Rp 6.177 with a share of labor of 43,25%. Thus, it can be seen the profit of the home industry “Jipang Gareng Lutfi" amounting to Rp 8.106 or with the level of profit 56,75%.